AIM2 in regulatory T cells restrains autoimmune diseases - Chou, Wei-Chun (Nature, 2021)
The inflammasome initiates innate defense and inflammatory response by activating caspase-1 and pyroptotic cell death in myeloid cells(1,2). It is comprised of an innate immune receptor/sensor, pro-caspase-1, and a common adaptor molecule, ASC (apoptotic speck-containing protein with a CARD). Consistent with their pro-inflammatory function, caspase-1, ASC and NLRP3 exacerbate autoimmunity during experimental autoimmune encephalomyelitis (EAE) by enhancing IL-1β and IL-18 secretion in myeloid cells(3–6). Here we reveal an unexpected function of a DNA-binding inflammasome receptor, AIM2 (Absent in Melanoma 2)(7–10), in T regulatory cells (Tregs) to restrain two models of autoimmunity (experimental autoimmune encephalomyelitis and T cell-mediated colitis) by studying whole-body and Treg-specific Aim2(–/–) mice. AIM2 is highly expressed by human and mouse Tregs, with its expression induced by TGF-β and its promoter occupied by transcription factors associated with Tregs, including Runx1, Ets1, Bcl11b and CREB. RNA-seq, biochemical and metabolic analyses revealed that AIM2 attenuates Akt-phosphorylation, mTOR, c-Myc and glycolysis, but promotes lipid oxidative phosphorylation in Tregs. Mechanistically, AIM2 interacts with the RACK1/PP2A-phosphatase complex to restrain Akt-phosphorylation. Lineage tracing demonstrates that AIM2 promotes the stability of Tregs during inflammation. While AIM2 is generally accepted as an inflammasome effector in myeloid cells, this report reveals a T cell-intrinsic role of AIM2 in restraining autoimmunity by diminishing Akt-mTOR signaling and altering immune-metabolism to enhance Treg stability.